Penerapan Ilmu Manajemen untuk Meningkatkan Sumber Daya Manusia Melalui Potensi yang Ada dalam Hal Sikap Peduli Lingkungan dan Menjadi Masyarakat Edukatif agar Tercapainya Pembangunan yang Berkelanjutan Desa Ciwalat Kec. Pabuaran, Kab. Sukabumi - Saputra, Yance; Yunus, Ahmad; Juniyansyah, Agung; Ratri, Tito Mustikaningrum; Hutapea, Zeriko; Sugiarti, Endang; Supratikta, Hadi (Jurnal PKM Manajemen Bisnis, 2024)
This community service project is titled "The Application of Management Science to Improve Human Resources through Existing Potentials in Environmental Awareness and Becoming an Educative Society to Achieve Sustainable Development in Ciwalat Village, Pabuaran District, Sukabumi Regency." This project was conducted on Sunday, June 2, 2024, and was attended by 20 students and 6 supervising lecturers from Pamulang University. The general objective of this community service activity is the application of management science to improve human resources (HR) through existing potentials in terms of environmental awareness and becoming an educative society in sustainable village development. Empowering village resource potentials to enhance the village economy and creating Ciwalat Village as a smart village and a leading village in Sukabumi Regency. The methods used include surveys, direct material delivery, as well as simulations and discussions on management, financial management, product marketing, and the application of human resource management (HRM). This community service activity successfully provided understanding to the community, especially MSMEs, regarding product marketing conducted through digital marketing via the marketplace (Shopee) in an effort to develop the businesses or enterprises of the Ciwalat Village Community.